REFORMULASI PEMIDANAAN TERHADAP PENGGUNA NARKOTIKA DALAM SISTEM HUKUM PIDANA DI INDONESIA - Mona Minarosa (Fakultas Hukum Universitas Borobudur, 2023)
Narcotics abuse in Indonesia is increasing from year to year and is dominated by children and teenagers due to two factors, namely external factors and internal factors. The problem discussed in this research concerns the form of punishment and reformulation of punishment for narcotics users in the criminal law system in Indonesia. This research is empirical legal research as an attempt to approach the problem under study with real legal characteristics or in accordance with real life in society and is connected to an analysis of statutory regulations. The form of punishment for narcotics users in the criminal law system in Indonesia is regulated in Law Number 35 of 2009 concerning Narcotics, specifically Articles 111 to Article 148. In preventing the abuse of narcotics use, the type of crime carried out is not only based on the sanctions contained in Article 10 of the Criminal Code, namely death penalty, life imprisonment, imprisonment and fines, but there is a reformulation of punishment in the criminal law system in Indonesia, namely penal measures and non-penal measures.